THE EFFECT OF PICTURE CARD GAMES ON VOCABULARY ACQUISITION OF CHILDREN 5-6 YEARS OLD: PENGARUH PERMAINAN KARTU GAMBAR PADA PEMEROLEHAN KOSA KATA ANAK USIA 5-6 TAHUN - NUR LAILI MUS’ADAH; AHMAD FACHRURRAZI (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2020)
Picture card games are one type of game that can support early childhood education in aspects of language development to improve the acquisition of children's vocabulary. Mastery of vocabulary has an important function, because children who master a lot of vocabulary, tend to have high self-esteem.The purpose of this study is to describe more in-depth about the effect of picture card games on the acquisition of children's vocabulary. The method used is a quantitative research method using the design of the One Group Pretest-Posttest. Sempel used in this study were 19 children in group B TK Aisyiyah Bustanul Athfal 57 Surabaya. Data were collected from the results of performance test observations, with a performance sheet observation instrument. The data analysis technique uses the t test formula.The results of this study indicate that t count obtained value (36.66) greater than the value of t table (1.79) at the significance level of 0.05 and (2.55) at the 0.01 significance level, then the Zero Hypothesis is rejected so the Hypothesis Work received. Thus it can be stated that